(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
We know that since time immemorial, humanity has tried to create an entertaining and pleasant environment for their recreation and cultural enjoyment. In parks around monuments of different countries, devices were created in different ways. Among them are the ancient gardens of Turan, Samarkand, Khiva, Bukhara, Timurids. The skillful use of water features, ornamental plants, and wonderful architectural techniques in landscape nature has made historical cities even more beautiful.